'Mindful' human resource management: combining Buddhist principles of enlightenment with diversity management. (31st August 2021) - Nilsson, Håkan; Kazemi, Ali
Over the last two decades, numerous organisational scholars have emphasised the importance of enhancing ethics and workplace diversity within organisations. The aim of the present article is to present a workplace diversity perspective on human resource management by advancing the notion of mindful human resource management that builds upon Buddhism's notions of wisdom, ethical conduct, and concentration, thus facilitating a steady form of attention and a non-judgmental state of mind. We propose that combining the three characteristics of the Buddhist path can help human resource managers to be more ethically minded, diversity conscious, compassionate, and caring in their decisions and actions.